Preparation of metal-semiconductor nanocomposites for photocatalysis - Phua, Li Ling (Nanyang Technological University, 2022)
A great deal of interest has been focused on nanocomposite materials, in particular for semiconductor nanomaterials recently as they are able to show distinctive properties when compared to their bulk equivalents. Noble metal-semiconductor nanocomposites can overcome the limitations of difficult electron-hole migration and low photocatalysis efficiency by enhancing photocatalysis. Due to energy shortage and pollution, green technology like semiconductor photocatalysis has been gaining a lot of attention by decomposing hydrogen and oxygen with the help of light. In this report, the bulk C3N4 samples are synthesize and exfoliated with different condition; Argon vs Air annealing. Platinum, Pt of 0.5 wt% is photodeposited onto the synthesized samples. Hydrogen evolution reaction, HER, to investigate the photocatalytic activities for H2 production, and material characterization like SEM, TEM, HAADF-STEM, FTIR and UV-Vis, to analyse the material properties, are carried out. With the result and findings, the exfoliated C3N4 , E-M-Air-Pt has a larger specific surface area and reactivity sites as compared to the bulk counterpart, B-M-Pt. Under visible light for 3 hours, the H2 production of E-M-Air-Pt and B-M-Pt is 2.894 and 0.5 mmol/g of H2 respectively. Under full spectrum for 3 hours, E-M-Air-Pt produce 5.317 mmol/g of H2, and B-M-Pt produces 2.266 mmol/g of H2. The production capability of E-M-Air-Pt is 5.79 and 2.346 time more effective than B-M-Pt in visible and full spectrum respectively. The large specific surface area and increase in active sites improve the efficiency of photocatalysis. In addition, the semiconductor-metal heterojunction boosts the efficiency of the electron and hole pair separation which enhances the overall photocatalysis effectiveness.